A comparative study of Venezuelan immigrants' pre- and post-migration concerns for their children in the United States and Colombia. - Aigerim Alpysbekova; Pablo Montero-Zamora; Mary H Soares; Carolina Scaramutti; Sumeyra Sahbaz; Maria Duque; Tara Bautista; Maria Fernanda Garcia; Christopher P Salas-Wright; Mildred M Maldonado-Molina; Melissa M Bates; Augusto Pérez-Gómez; et al. (PLoS ONE)
Research suggests that forced migration may lead to cultural stress and psychological distress. However, little is known about immigrant parents' pre- and post-migration concerns for their children's welfare. The present study examined the concerns of Venezuelan parents who migrated to the United States versus those who migrated to Colombia, and whether post-migration concerns were related to cultural stressors, mental health, and cultural identity. A sample of 609 Venezuelan immigrants completed surveys and responded to an open-ended prompt asking about pre- and post-migration concerns for children's welfare. Lack of safety was the most common pre-migration concern for Venezuelans in the U.S., whereas lack of food was the most common pre-migration concern for Venezuelans in Colombia. More years in the destination country since arrival were linked to heightened economic concerns and reduced worries about family separation. A positive link emerged between national identity and health-related concerns for children following migration. This knowledge can inform policies and programs to better support immigrant families as they navigate the challenges of forced migration.